Evaluating Pronunciation Segment Of Propower I Software - Puteh, Fatimah; Sabidi, Fatin Nuraini (2010)
Pronunciation skill has increasingly become one of the most important skills in acquiring comprehensible input in a conversation. The ProPower I Software offers a pronunciation programme to help users to improve their pronunciation. It is crucial to evaluate the segment before adopting any part of the programme into a language classroom. In fact, evaluate language softwares manage to help teachers to see the strengths and weaknesses of the programme. This study focused on the sufficiency of the content and how the elements of user-friendliness were used in the pronunciation segment. This study was also to find out what are the characteristics of the programme that motivate the users to continue using the pronunciation segment of ProPower 1 Software. This study involved 15 third year and 15 final year students from TESL programme, UTM. Software evaluation matrix was used as an instrument for the data collection. It contained 2 sections which were evaluation matrix and structural form of questions. From the findings, majority of the respondents agreed that the content was sufficient for the low and intermediate level of users. Most of the respondents stated that the elements of user-friendliness used in the programme were ease in navigation of the programme, consistent use of the buttons and icons and acceptable use of symbols and icons. Audio, games and voice recording were proven to be the most influential factors among the respondents that motivate the users to continue using the pronunciation segment of ProPower I Software.